1987
DOI: 10.4049/jimmunol.139.7.2398
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional properties of serine esterases in acidic cytoplasmic granules of cytotoxic T lymphocytes.

Abstract: Percoll gradient fractions of homogenates of murine cloned cytotoxic T lymphocytes (CTL) were analyzed for the trypsin-like enzyme alpha-N-benzyloxy-carbonyl-L-lysinethiobenzyl ester (BLT) esterase recently described in CTL homogenates. Enzymatic activity was found in three areas of the gradient: the dense cytolysin containing granules; a light granule fraction; and a variable amount in the soluble fraction at the top of the gradient. Gel filtration columns showed a major peak of BLT esterase activity eluted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We also tested their chemical integrity at different pH values because GzmA can be stored in slightly acidic cytotoxic granules inside CTLs. [21] In these experiments, we observed that the amide compound 4 was stable in basic and acid media, whereas the thioester 3 was more stable than the carboxylic ester analogue 2 at acidic pH (Figure 2 ). Finally, we confirmed by HPLC‐MS that the Ac‐IGNR amide derivative could be cleaved by recombinant hGzmA (Figure S1), thus we focused on this scaffold for the generation of fluorogenic GzmA substrates.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We also tested their chemical integrity at different pH values because GzmA can be stored in slightly acidic cytotoxic granules inside CTLs. [21] In these experiments, we observed that the amide compound 4 was stable in basic and acid media, whereas the thioester 3 was more stable than the carboxylic ester analogue 2 at acidic pH (Figure 2 ). Finally, we confirmed by HPLC‐MS that the Ac‐IGNR amide derivative could be cleaved by recombinant hGzmA (Figure S1), thus we focused on this scaffold for the generation of fluorogenic GzmA substrates.…”
Section: Resultsmentioning
confidence: 79%
“…As shown in Figure 2, we found that compounds 2 and 3 were completely hydrolyzed in Tris buffer (pH 7.4) whereas compound 4 was fully stable under the same experimental conditions (purity >95 %). We also tested their chemical integrity at different pH values because GzmA can be stored in slightly acidic cytotoxic granules inside CTLs [21] . In these experiments, we observed that the amide compound 4 was stable in basic and acid media, whereas the thioester 3 was more stable than the carboxylic ester analogue 2 at acidic pH (Figure 2).…”
Section: Resultsmentioning
confidence: 97%